Implementasi Program Rumah Tidak Layak Huni di Kabupaten Asahan Pada Tahun 2019 - Achmad Hamdy; Badaruddin & Humaizi Badaruddin & Humaizi; Humaizi Humaizi (Universitas Medan Area, 2021)
AbstractAsahan District is one of the many districts in Indonesia that has implemented a rehabilitation program for unfit for habitation because there are still some Asahan people who are unable to meet their basic needs, namely a livable house. The purpose of this study is to determine the implementation, obstacles and responses of the community to the uninhabitable house rehabilitation program in Asahan Regency in 2019. The theories used in this study consist of phenomenological development paradigms, development definitions, public policies, public policy implementation. (policy implementation) with George Edwards' approach, consisting of communication, human resources, the tendency of the implementer, and the position of the implementer. Qualitative analysis was used with each informant as a source of information, consisting of 1 key informant, 1 main informant and 6 additional informants. The results showed that the implementation of the Rehabilitation Program for Unworthy Houses (RTLH) in Asahan Regency was good, through communication, human resources, disposition and bureaucratic structures, implemented as an integral part of achieving the effectiveness of social development programs for the feasibility of roofs, floors and walls. Implemented social development is defined as the achievement of social welfare with the principles of development that is not centralized and not top down; Human resource constraints with limited staff and community delays in completing the program can be handled properly. The response of the community who benefited from the RTLH Rehabilitation program was good, indicated by the support for program achievements and their acceptance of the requirements that had to be met both administratively and the criteria for the use of assistance.